JAMINAN INDUSTRI HALAL DI NEGARA SINGAPURA DAN TAIWAN - Anatasha, Syaira; Malahayatie, Malahayatie (Al Dzahab, 2024)
Purpose: This study examines and compares the halal assurance processes in Indonesia, Taiwan, and Singapore. In addition, this study aims to assess the consequences of each system on the growth of the halal sector on a global and regional scale. Design/Methodology/Approach: This research utilises a comparative case study methodology with a qualitative approach. Through the investigation of official documents, data was collected. Regulations, certification requirements, and industry reports from each country were analyzed in the documents. Manufacturers, customers, and representatives from halal certification authorities were interviewed. To gain a first-hand understanding of the certification process and the application of regulations, field observations were also conducted. Findings: The findings show that Singapore, Taiwan, and Indonesia have different strategies for implementing halal assurance. Majlis Ugama Islam Singapura (MUIS) in Singapore operates a rigorous and globally renowned certification program. Taiwan concentrates on food and cosmetic products through the Taiwan Halal Integrity Development Association (THIDA). With the support of the world's largest Muslim community, Indonesia, the Halal Product Guarantee Agency (BPJPH), has established a comprehensive and integrated system. These different strategies affect the efficacy of halal products and consumer confidence in each country. Research Implications: The results of this study show how harmonization of international halal certification and standards can improve consumer confidence and increase international trade in halal goods. In addition, by incorporating best practices from other countries, policymakers and industry players can improve their halal assurance systems with the help of this study. This harmonization can guarantee more reliable halal products to Muslim consumers around the world and improve the global halal market position.